The Effects of British Columbia’s Vacancy Tax and Foreign-buyer Tax Act on the Supply of New Residential Housing in Vancouver - Hu, Jingting (Université d'Ottawa | University of Ottawa, 2018)
On Aug 2, 2016, the government of British Columbia introduced the Vacancy Tax and Foreign-buyer Tax Act. This tax act was introduced in a surprise move by the provincial Liberal government. Based on early preliminary data (Bloomberg, 2017), it is reasonable to conclude that from a market demand perspective, the new tax acts have been quite successful in controlling residential housing prices in Vancouver. However, the effect of the tax acts on the supply side of Vancouver’s housing market remains mixed and unclear. This is especially true in regards to the supply of new residential buildings, which is a key element of the total housing supply. The main goal of this paper is to investigate the effect of British Columbia’s Vacancy Tax and Foreign-buyer Tax Act on the supply of new residential housing in Vancouver, which is measured by the number of new builds (housing starts) and the associated value of these properties (value of residential housing building permits). The conceptual framework of this study exhibits a fixed effects model and DID design based on a panel dataset that is constructed from customized tabulations from Bloomberg and Thomson Reuters DataStream. Unlike most of the relevant literature (such as Gyourko and Saiz (2006) and Quigley and Raphael (2005)) suggests, the empirical results of this study indicate that British Columbia’s Vacancy Tax and Foreign-buyer Tax Act have a positive impact on the supply of new residential housing in Vancouver. More specifically, the tax act has a strong positive causal impact on the number of new residential builds (housing starts) and a weak positive causal relationship on the total book value of these properties (value of residential housing building permits). This outcome is favourable to the policymaker as the tax act did not suppress the supply of new residential housing; in fact, the act seems to encourage builders to commit to constructing more residential houses with no significant increase in the value of the property building permit, which is a positive step towards creating more affordable housing.